Knowledge and the Sociology of Education - Young, Michael (Acta Paedagogica Vilnensia, 2020)
This paper does not go into detail concerning the current debate around the idea of “powerful knowledge”, however, a brief account of the history and context of the sub-discipline as it has developed in England, is presented. For that purpose, some references to the important works of Basil Bernstein are explicated. It was he after all, following the critical reception of his early work on linguistic codes, who first argued that knowledge, or as it is sometimes expressed “the stuff” and not just “the who” of education, was crucial to any serious debate. Some hot points in the debate between Bernstein and Michael Young are presented. The suggestion is given that differently from Bernstein ideas to take into account „pedagogical code“ in the knowledge reproduction we have to begin with the distinction between memorisation of knowledge which is close to the idea of consumption, and developing a relationship to knowledge which has more affinity with becoming a member of a community.